2018
DOI: 10.30848/pjb2019-2(9)
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and bioactivity from Jatropha Curcas L. leaves by steam distillation.

Abstract: Jatropha curcas L. has biological activities that can contribute to find new products. In this study, steam distillation at laboratory scale was applied to J. curcas leaves to assess the yield of essential oil and the bioactivity of the hydrolate. The effect of steam flow and bed porosity on the extraction yield was also determined, where it was observed that residence time was one of the influential factors in the yield of essential oil. The extracts were analyzed by GC-MS. Dibutyl phthalate, phytol, and diis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, obtained results were in context with results obtained by Ingle et al (2017) on the 3 rd instar larvae of S. litura. The toxic activity of jatropha oil is due to the presence of hydrolates which were reported previously for their toxicological effect against S. littoralis larvae besides their antioxidant and antibacterial activities (Calvo, 2012 andSoto-Armenta et al, 2019). In addition, it was reported that Jatropha contains high amounts of phenolics, esters, and flavonoids, which proved to have high larvicidal activity (Oskoueian et al, 2011).…”
Section: Insecticidal Activity Of Tested Oilsmentioning
confidence: 76%
See 1 more Smart Citation
“…Furthermore, obtained results were in context with results obtained by Ingle et al (2017) on the 3 rd instar larvae of S. litura. The toxic activity of jatropha oil is due to the presence of hydrolates which were reported previously for their toxicological effect against S. littoralis larvae besides their antioxidant and antibacterial activities (Calvo, 2012 andSoto-Armenta et al, 2019). In addition, it was reported that Jatropha contains high amounts of phenolics, esters, and flavonoids, which proved to have high larvicidal activity (Oskoueian et al, 2011).…”
Section: Insecticidal Activity Of Tested Oilsmentioning
confidence: 76%
“…β-stigmasterol has acaricidal activity while phytol has antimicrobial, anti-inflammatory, anticancer, and diuretic activities (Rajeswari et al, 2012). Some studies reported that aqueous and methanolic extracts had insecticidal activity specifically against dipteran insects (Kovendan et al, 2011;Tomass et al, 2011;Juliet et al, 2012;Reichel et al, 2013;Chauhan et al, 2015;Khattak et al, 2015;and Soto-Armenta et al, 2019).…”
Section: Introductionmentioning
confidence: 99%